Compiling What to How. - Bodik, Rastislav (Communications of the ACM, 2012)
The article discusses a paper by Viktor Kuncak et al., published in the same issue, in which a computer programming language is presented with integrated declarative programming. The author argues that the paper makes several important contributions to declarative programming, saying that it increases the power of the Scala host language, creates debugging support, and compiles speciation to create a solver code.